2018
DOI: 10.3389/fmars.2017.00435
|View full text |Cite
|
Sign up to set email alerts
|

Size Class Dependent Relationships between Temperature and Phytoplankton Photosynthesis-Irradiance Parameters in the Atlantic Ocean

Abstract: Robinson et al. Temperature and Phytoplankton Size Class Photosynthesis parameters at sea water temperatures up to 8 • C during monospecific blooms and the Uitz et al. (2008) method to derive PE parameters of mixed populations over the temperature range from 8 to 18 • C. Both methods exhibited similar relationships between pico-phytoplankton PE parameters and temperatures >18 • C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 122 publications
(231 reference statements)
0
14
0
Order By: Relevance
“…However, in regions with different underlying physical forcing that experience a smaller range in temperature, such as the Arabian Sea and open ocean gyres, the relationship between temperature and P B m is less obvious (this study; [40,41,105,107,110]). In such regions, chlorophyll-a concentration and the taxonomic and size structure of the phytoplankton community may be better indicators of variability in P B m [38,41,86,107,108]. The initial slope of the P-I curve seems to be more difficult to predict based on empirical relationships with physico-chemical conditions (this study, [41,86]), and it has been suggested that the simplest approach to estimate α B would be to relate α B to the assimilation number [33,110,111].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…However, in regions with different underlying physical forcing that experience a smaller range in temperature, such as the Arabian Sea and open ocean gyres, the relationship between temperature and P B m is less obvious (this study; [40,41,105,107,110]). In such regions, chlorophyll-a concentration and the taxonomic and size structure of the phytoplankton community may be better indicators of variability in P B m [38,41,86,107,108]. The initial slope of the P-I curve seems to be more difficult to predict based on empirical relationships with physico-chemical conditions (this study, [41,86]), and it has been suggested that the simplest approach to estimate α B would be to relate α B to the assimilation number [33,110,111].…”
Section: Discussionmentioning
confidence: 91%
“…Over the past three decades, considerable efforts have been made to establish a global database of P-I parameters ( [2,31,33,86]; this study) and to decipher their empirical relationships with physico-chemical and optical properties to enable prediction of photosynthetic parameters on regional and global scales [38,40,41,[105][106][107][108]. The observed relationships between physico-chemical conditions and P-I parameters in the present study confirmed earlier observations that temperature may be a good predictor of the assimilation number (P B m ), especially in coastal regions and temperate oceanic regions where temperature and associated water column stability dictates seasonal changes in the taxonomic and size structure of phytoplankton communities [40,86,109].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It thus would appear that the high primary production at the DCM during PEACETIME was due not only to enhanced levels of phytoplankton biomass but also to the presence of a diatom-rich community characterised by high photosynthetic efficiency. These results stress the importance of incorporating the linkage between community structure and photophysiological parameters to improve the application of bio-optical productivity models over diverse ecological and biogeographic settings (Robinson et al, 2018;Uitz et al, 2010;Uitz et al, 2012).…”
Section: Phytoplankton Photophysiology and Productivitymentioning
confidence: 75%
“…The size-structure of the phytoplankton affects export of large aggregates (Boyd and Newton, 1999), with large cells thought to contribute more to the flux of carbon at depth than smaller phytoplankton, at similar levels of total chlorophyll (Guidi et al, 2009), acknowledging small-celled carbon export can be significant (Richardson, 2019). The photosynthetic rate of phytoplankton, for a given concentration of total chlorophyll, has been shown to depend on size-structure (Platt and Jassby, 1976; Fernández et al, 2003; Morán et al, 2004; Uitz et al, 2008; Álvarez et al, 2016; Brewin et al, 2017b; Curran et al, 2018; Robinson et al, 2018a,b). Biological heating by phytoplankton is influenced by the chlorophyll-specific absorption coefficient, which changes with size (Bricaud et al, 2004; Devred et al, 2006; Uitz et al, 2008; Brewin et al, 2011).…”
Section: Resultsmentioning
confidence: 99%